HAJJ TRANSPORTATION OF NETHERLANDS EAST INDIES, 1910-1940 - Tantri, Erlita (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2013)
This article is about Hajj transportation of Netherland Indies in during the years of 1910-1940. The focus of this article is the mechanism of the Hajj transportation and its significance since eighteenth century. It is based on that historical phmomenon, that this paper will examine the hajj transportation in the past related to regulation and problem and why it was important to control hajj ship transportation by using archives and authorities' report as main sources and other secondary sources. Historically, since eighteenth century, even until today, going to hajj or pilgrimage was very interesting and attractive for native Muslim in Netherlands East Indies (Indonesia), especially for gaining religious requirement, social pride and Islamic ideas. The phenomenon can be seen from the increase and the stable number of the pilgrims from Indonesia which had attracted much interest from many parts of stake holders such as from Hijaz (Arabian government). In relation to that, it is worth noting that ship was an important transport to convey pilgrim from and to Indonesia and thus, business of hajj transportation become a field of contention between state authority and private ship businesses. It is based on that historical phenomenon, that this paper will examine the hajj transportation in the past related to regulation and problems and why it was important to control hajj ship transportation by using archives and authorities report as main sources and other secondary sources. Hajj transportation was a profitable business (even until today) that increased competition among British, Malay, Arabic, and Dutch shipping companies. Completion and regulation from ships and authority did not give better services for native pilgrims besides poor condition, discomfort and suffering of pilgrimage. However, hajj transportation had to be controlled, especially to restrain problems of moekimans and movement ideas from Hijaz.